PENGARUH ICE BREAKING TERHADAP SEMANGAT BELAJAR PESERTA DIDIK DI MTS TERPADU H. ABDUL KARIM SYU’AIB GUGUAK RANDAH KABUPATEN AGAM - Lathifah Azzahra; M. Isnando Tamrin; Latifah Hanum (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This research refers to the lack of enthusiasm for students' learning in Al-Qur'an Hadith subjects. This happens because educators do not provide interesting innovations in learning, so that students easily get bored and sleepy during the learning process. Ice breaking is a simple activity and quite easy to do, it only requires creative ideas from the educator. Ice breaking functions to change the stiffness during learning to become relaxed and relaxing, and reduces feelings of boredom and sleepiness in the learning process. The research method used in this research is a qualitative descriptive method and to collect research data, researchers conducted observations, interviews and case studies that occurred where the research took place.